Histori, Urgensi Dan Prinsip Penulisan Mushaf Al-Qur’an Standar Indonesia - Huda, Nurul (LPPM STAI La Tansa Mashiro, 2024)
The Qur'an is the lifeblood of Muslims. The values contained in it, should flow swiftly in their lives, at every moment and opportunity. For this reason, considering the urgency of the Qur'an for Muslims around the world, various activities related to it are continuously organised; in the form of reading the editorial/text, studying the substance/interpretation, elaborating the meaning/interpretation, memorising and maintaining the kemushafannya. The problem is that the people who access the Qur'an are not only Arab Muslims as natives, but also non-Arab Muslims ('ajam) who do not know Arabic at all. For this reason, efforts to make it easier for non-Arab Muslims continue to be made. Thus, various quick methods to read it emerged. In Indonesia, the Qiraati Method by KH Dahlan Salim Zarkasyi, the Iqra Method by KH As'ad Humam, al-Barqi, Mafaza, and so on emerged. Even to make it easier to read, the Qur'an in Indonesia was standardised by the Lajnah Pentashih al-Qur'an of the Ministry of Religious Affairs of the Republic of Indonesia through the publication of Mushaf al-Quran Standar Indonesia (MASI) after the Minister of Religious Affairs Decree (KMA) No. 25 of 1984 concerning the Determination of the Standard Qur'an. Keywords: Writing, Standard, Mushaf, al-Qur'an